Hi, i have the following ODE system in x und y:
x'(t) = x - y - x*(x²+y²)
y'(t) = x + y - y*(x²+y²)
By use of polar coordinates
x(t)=r(t) * cos ( @(t) )
y(t)=r(t) * sin ( @(t) )
[@ = theta]
it is supposed to be transformed into the system
r'(t) = r - r³
@'(t) = 1
how is that done?
My ideas so far:
I derive x(t)=r(t) * cos ( @(t) ) and obtain
x'(t) = r'(t)*cos(@(t)) + r(t)*(-sin(@(t)))*@'(t)
y'(t) = r'(t)*sin(@(t)) + r(t)*cos(@(t))*@'(t) (1)
Now I replace x(t) by r(t)*cos (@(t)) in the original ode, i.e.
x - y - x*(x²+y²) -> r*cos@ - r*sin@ - r*cos@*r²
x + y - y*(x²+y²) -> r*cos@ + r*sin@ - r*sin@*r² (2)
now identify the expessions in (1) with those in (2) leads to
r'(t)*cos(@(t)) + r(t)*(-sin(@(t)))*@'(t) = r*cos@ - r*sin@ - r*cos@*r²
r'(t)*sin(@(t)) + r(t)*cos(@(t))*@'(t) = r*cos@ + r*sin@ - r*sin@*r²
now this should be equal to the given solution
r'(t) = r - r³
@'(t) = 1
but so far i failed to find an adequate transformation...
thanks for your help
x'(t) = x - y - x*(x²+y²)
y'(t) = x + y - y*(x²+y²)
By use of polar coordinates
x(t)=r(t) * cos ( @(t) )
y(t)=r(t) * sin ( @(t) )
[@ = theta]
it is supposed to be transformed into the system
r'(t) = r - r³
@'(t) = 1
how is that done?
My ideas so far:
I derive x(t)=r(t) * cos ( @(t) ) and obtain
x'(t) = r'(t)*cos(@(t)) + r(t)*(-sin(@(t)))*@'(t)
y'(t) = r'(t)*sin(@(t)) + r(t)*cos(@(t))*@'(t) (1)
Now I replace x(t) by r(t)*cos (@(t)) in the original ode, i.e.
x - y - x*(x²+y²) -> r*cos@ - r*sin@ - r*cos@*r²
x + y - y*(x²+y²) -> r*cos@ + r*sin@ - r*sin@*r² (2)
now identify the expessions in (1) with those in (2) leads to
r'(t)*cos(@(t)) + r(t)*(-sin(@(t)))*@'(t) = r*cos@ - r*sin@ - r*cos@*r²
r'(t)*sin(@(t)) + r(t)*cos(@(t))*@'(t) = r*cos@ + r*sin@ - r*sin@*r²
now this should be equal to the given solution
r'(t) = r - r³
@'(t) = 1
but so far i failed to find an adequate transformation...
thanks for your help